2009
DOI: 10.1021/jp905733d
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Complexation Study of Metal Ions with Cysteine

Abstract: Metal complexes of cysteine have been studied using a density functional theory based method together with a continuum solvation model. Complexation geometries for metal complexes of cysteine with Zn(2+), Mg(2+), Ca(2+), Fe(3+), and Mn(2+) have been determined. Different coordination modes have been considered for MCys(2) and MCys(3) complexes. Complexation energies have been determined, and they have been corrected with (empirical) metal- and ligand-specific parameters, the latter of which was determined sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
(68 reference statements)
0
28
0
Order By: Relevance
“…Several studies report this methodology to determine the strength of binding of metal cations and ligands. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies report this methodology to determine the strength of binding of metal cations and ligands. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47] …”
Section: Resultsmentioning
confidence: 99%
“…It was found that the peripheral groups bonded to the anchoring atom that binds to the metal cation modulate the interaction strength. Pesonen et al 35 performed a density functional theory (DFT) study of the interaction of mono-and bidentate ligands with metal cations, where the interaction with the bidentate ligands was stronger than that with monodentate ones. The size of the cation, its softness and the stabilization energy of ligand's chelation directly affected the coordination preferences.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…This functional has been shown to give reasonable optimized ZnAS and ZnAN bond lengths in numerous studies of zinc complexes [49][50][51][52]. In order to speed up the calculations, the multipole accelerated resolution of identity for J (MARI-J) approximation method [53], as implemented in Turbomole [54], has been used.…”
Section: Methodsmentioning
confidence: 99%
“…The low-molecular-weight thiols, such as L-cysteine (L-Cys), homocysteine (Hcy), and glutathione (GSH), which play important roles in many physiological and biochemical application [36]. L-Cys molecule contains a -SH which makes it unique among the amino acids [37]. So we want to synthesize a material containing -SH for detection of metal ions based on above reasons.…”
Section: Introductionmentioning
confidence: 99%